Terapi Nutrisi Pasien di Intensive Care Unit (ICU) - Santosa, Budi; Suwarman; Pradian, Erwin (Jurnal Komplikasi Anestesi, 2020)
Nutrition is important in critical patient care. Malnutrition may lead to poor outcome of the patient in ICU, including increases morbidity, mortality, and length of stay. Patient in ICU also experienced increased metabolism and catabolism which can lead to malnutrition. Therefore, the provision of nutrition for patients in the ICU needs a special care. The nutritional requirement of critical ill patients depend on the severity of the disease and previous nutritional status. To achieve the demand of nutritional demand can be given enterally, parenterally or both.